The Difference of Satisfaction Level in BPJS Health Insurance Patient and Non Insurance Patient toward Health Service - Arlina Dewi; Naufal Kurnia Ramadhan (International Journal of Public Health Science (IJPHS), 2016)
National Health Insurance (JKN) developed in Indonesia is part of the National Social Insurance System (SJSN). One way to assess the services quality is to measure the patient satisfaction level. This research is a quantitative research with the cross sectional research design. The subjects of this research were the BPJS health insurance patients and non insurance patients with 200 people as the samples. The data was analyzed by the independent t-test, gap analysis, CSI (Customer satisfation index) and IPA (Importance performance analysis). The result showed that significant (ρ value >0,05) in all dimensions which mean that there is no difference of patient satisfaction level in Social Security Organizing Body (BPJS)  participants and non insurance patients toward health services in Negara General Hospital. The biggest satisfaction in non insurance patients is on the Assurance variable (-1,002) and the smallest satisfaction is on the Tangibles variable (-1,357) and the biggest satisfaction of BPJS health insurance patients is on Assurance variable (-1,085) and their smallest satisfaction is on Responsiveness variable (-1,367). The non insurance patients gap is (-0,217) and the BPJS health insurance patients gap is (-1,206), both of them were classified into low satisfaction level. The result of Importance performance analysis value of non insurance patient showed Responsiveness attributes that should be prioritized and improved while in BPJS health patients showed Responsiveness and Reliability attributes that should be prioritized and improved by Negara General Hospital.